Pemberitaan “Political Will” Wujudkan Keandalan Transportasi Umum Jakarta Pada Kompas.id - Farahainnisa, Inda; M, Muharom; Ningsih, Dwi Fitria; Putri, Wulandari; Al Ghany, Nazwa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The article “Political Will Realizes the Reliability of Jakarta’s Public Transportation” from Kompas.id has provided basic information. The issue of public transportation discussed is indeed centered on the city of Jakarta, a metropolitan city that is always busy and has high traffic volume and high congestion, even ranking as the 7th most congested city in the world. Another problem is that Jakarta is not a single city that stands alone, this city is supported by several other supporting cities such as Bogor, Depok, Tangerang, and Bekasi. The cities above also depend on public transportation in Jakarta which is usually where their people work, therefore the solution offered by Pramono Anung and Rano Karno must be comprehensive and not only fair to certain areas. This issue is very important to discuss because according to Tempo, there are 22.4 million vehicles passing through Jakarta in 2022. In addition to causing endless congestion, the large number of motor vehicles also causes other problems such as poor environmental and air quality in Jakarta. Therefore, the program that will be launched by Pramono Anung and Rano Karno later must be a breakthrough in reform in the world of public transportation in Jakarta, not just a political promise for image.